Optimization of Mathematics Learning Interest and Achievement through Group Investigation Type Cooperative Learning Model in Online Learning - Anggie Yudistira Aditya; Hammam Al Faruq; Dwi Susanto (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2025)
This study aims to evaluate the effectiveness of the Group Investigation (GI) cooperative learning model in enhancing students' interest and achievement in mathematics at SMP Unggulan Aisyiyah Bantul. The background of this research is the low interest and achievement in mathematics among students, who often perceive mathematics as a complex subject. The GI model was chosen for its potential to foster active collaboration and deep understanding. The research method used is Classroom Action Research (CAR), with two cycles, each consisting of two meetings. The research sample involved 28 students participating in online learning implementing the GI model. Data were collected through pretests and posttests to measure learning outcomes and questionnaires to assess students' interest in learning. The results showed a significant increase in students' learning outcomes after implementing the GI model. In the first meeting of the cycle I, the average posttest score reached 87.89, an increase of 7 points from the pretest. In the second meeting of cycle II, the average posttest score reached 98.93, an increase of 1.07 points from the previous meeting. Additionally, students’ interest in learning showed consistent improvement across enjoyment, attention, interest, and engagement indicators. In the second meeting of cycle II, 86% of students reported feeling very happy, 64% showed excellent attention, 61% exhibited very high interest, and 61% demonstrated very high engagement. In conclusion, implementing the Group Investigation cooperative learning model effectively improves students’ learning outcomes and interest in online mathematics learning. The integration of technology, such as the Zoom platform, supports effective collaboration in virtual environments and facilitates interactive learning that enhances material comprehension.